Desenvolvimento de jogo educacional para o estímulo ao aprendizado do ensino de Ciências Biológicas e Anatomia Ocular - Rocha, Rafael Lopes [UNIFESP] (2021)
Introduction: The technological advancement helped to develop new tools to help the understanding of complex subjects that demand different pedagogical didactic approaches. Using mobile technology and internet people seek information that became faster and accurate. Although there is no guarantee the information is totaly true. To develop tools based on books and scientific research ensure the quality of the information. Goal: the study aims to elaborate theoretical content related to basic concepts of biological sciences and ocular anatomy to develop a game-type tool to aid in the study of basic concepts of biological sciences and ophthalmology using software development methodologies. Results: Based on study of biological sciences and software development methodologies to develop a executable tool. Conclusion: by using the concepts of Software Engineering and adopting requirements based on established benchmarks the development of prototypes for educational tools allows study of test cases, validation requirements and implementation of systems resulting in support tools to aid the study of biological sciences.